Response to comment on "point defect structure of La-doped SrTiO3 ceramics with colossal permittivity". (1st January 2021) - Qin, Mengjie; Gao, Feng; Cizek, Jakub; Yang, Shengjie; Fan, Xiaoli; Zhao, Lili; Xu, Jie; Dong, Gaogao; Reece, Mike; Yan, Haixue
Abstract: Materials with colossal permittivity (CP) have attracted wide interest and have tremendous potential application in super-capacitors [1] . Many materials with the colossal permittivity have been fabricated, such as Cu3 Ti4 O12 [2–6], TiO2 [7–10], BaTiO3 [11], and SrTiO3 [12–15], etc. However, the exact physical mechanisms and explanations for generating CP are still unclear. In our previous publication "Point defect structure of La-doped SrTiO3 ceramics with colossal permittivity" [16], we investigated point defects in pure SrTiO3 and La-doped SrTiO3, and reported that the origin of CP in La-doped SrTiO3 ceramics is related to a sharp polarization increase resulting from defects dipole structure. Recently, A. Tkach et al. commented on the publication and put forward some different viewpoints. In this letter, we would like to discuss the related issues and reply to the comments. Graphical abstract: Image, graphical abstract